Pendidikan: Pengertian pendidikan dan unsur-unsur pendidikan - Maghfiroh, Choirunnisa Maulidia (Maliki Interdisciplinary Journal, 2024)
The purpose of this essay is to define educational planning and discuss its components, tenets, and application. The most vital component of human life is education, including psychomotor, affective (attitude), and cognitive learning. Therefore, the ability for humans to experience the process is essential. Learning isa deliberate attempt to acknowledge the passing down of culture from one generation to the next. Curriculum, instructional resources, learners, teachers, and educational relationships are all involved in education. The subject matter being directed (students), the person guiding (teacher), the interaction between students and teachers (educational interaction), instructional resources and techniques, and curriculum are the components of education.